Surface-treated sol-gel silica particle, producing method of surface-treated sol-gel silica particle and toner external additive for electrostatic charge image development
Surface-treated sol-gel silica particles with specific properties address charge instability in toner additives, ensuring consistent toner performance and reducing image defects by maintaining charge stability across environmental variations.
Patent Information
- Application Number
- JP2023112966
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2043-07-10
AI Technical Summary
Conventional silica particles used as toner external additives exhibit charge instability due to environmental changes, leading to inconsistent toner properties and image defects.
Surface-treated sol-gel silica particles with specific siloxane units, particle size, circularity, refractive index, true density, volume resistivity, and moisture absorption characteristics are developed to maintain consistent charge and improve toner performance.
The surface-treated sol-gel silica particles provide stable charge and excellent printing characteristics across varying environmental conditions, reducing toner adhesion and image defects.
Smart Images

Figure 2025010768000001 
Figure 2025010768000002
Abstract
Description
[Technical field]
[0001] The present invention relates to surface-treated sol-gel silica particles, a method for producing the same, and an external additive for a toner for developing electrostatic images used for developing electrostatic images in electrophotography, electrostatic recording, etc. [Background technology]
[0002] Dry developers used in electrophotography and the like can be roughly divided into one-component developers that use toner itself in which a colorant is dispersed in a binder resin, and two-component developers in which a carrier is mixed with the toner, and when these developers are used for copying operations, in order to have process suitability, the developer needs to be excellent in flowability, caking resistance, fixing ability, charging ability, cleaning ability, etc. In particular, in order to improve flowability, caking resistance, fixing ability, and cleaning ability, inorganic fine particles are often used as an external toner additive.
[0003] However, the dispersibility of inorganic fine particles has a large effect on toner properties, and when the dispersibility is non-uniform, the desired properties of fluidity, caking resistance, and fixability cannot be obtained, and cleaning properties become insufficient, causing toner adhesion on the photoreceptor, which may cause image defects such as black dots. In order to improve these points, various proposals have been made in which the surfaces of inorganic fine particles are hydrophobized.
[0004] Recently, there has been a demand for faster copying machines and lower energy consumption, and toners are now required to have higher resistance to deterioration than conventional toners. If the toner does not have high resistance to deterioration, the toner's transfer efficiency cannot be maintained at a high level from the beginning to the end of use. As one of the countermeasures, a toner deterioration suppression technology has been proposed that utilizes the spacer effect of a large particle size toner external additive (Patent Documents 1 and 2).
[0005] In addition, as a toner external additive, a small particle size toner external additive and a large particle size toner external additive are often used in combination. Due to the presence of a large particle size toner external additive attached to the toner particle surface, the frequency with which the small particle size toner external additive attached to the nearby toner particle surface is directly subjected to external forces such as shear force and impact force is reduced, and the small particle size toner external additive can be prevented from being buried in the toner particle surface due to the external force (spacer effect), making it possible to suppress toner deterioration.
[0006] In addition, by adding a large particle size toner external additive, the toner becomes easier to separate from the photoreceptor, the toner on the photoreceptor is quickly transferred onto the paper, and the transfer efficiency can be maintained at a high level, so it is thought that the large particle size toner external additive also functions as a transfer aid.
[0007] Fumed silica particles produced by the conventional combustion method have been used as a large-diameter toner external additive that is expected to have a spacer effect. However, in recent years, it has become possible to obtain large-diameter spherical silica particles with a uniform particle size distribution by the sol-gel method, and a technology has been proposed in which spherical silica particles with an average particle size of about 50 nm to 150 nm are used as an external additive (Patent Document 3).
[0008] It has also been disclosed that the use of large-diameter monodispersed spherical silica with a true specific gravity of 1.9 or less is effective in suppressing the embedding of external additives and maintaining high developability and transferability from the beginning to the lapse of time (Patent Document 4). This low-specific-gravity monodispersed spherical silica rolls and is therefore likely to be interposed between the blade and the image carrier, providing an effective friction reduction effect and is also known to be effective in improving cleaning performance (Patent Documents 4 and 5).
[0009] However, when the particle size of spherical silica particles is increased, the surface area per unit mass of the silica particles decreases, so the charge amount decreases, and the Coulomb force that governs the adhesive force between the silica particles and the toner particles weakens, so that the silica particles are less adhesive to the toner particles and more likely to fall off the toner particles. When silica particles fall off the toner particles, the detached silica particles and toner particles cause contamination of the photoconductor, charging roll, and developing roll, and chipping of the cleaning blade, and it is also known that image defects due to contamination of these members, etc. occur (Patent Document 3).
[0010] In general, the charge amount of the toner and silica particles varies depending on the environment in which they are used, and at high temperature and humidity, the charge amount decreases, and the adhesion of the silica particles to the toner particles decreases, so that the silica particles become more likely to be detached from the toner particles, whereas at low temperature and low humidity, the charge amount becomes excessively high, and the charge on the toner is transferred to other objects, which easily causes image deterioration.
[0011] Thus, silica particles used as an external toner additive have a problem in that it is difficult to control the charge when the environment changes, and there has been a demand for silica particles with good charge controllability. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 06-027718 [Patent Document 2] Japanese Patent Application Publication No. 11-143118 [Patent Document 3] JP 2007-264142 A [Patent Document 4] JP 2001-066820 A [Patent Document 5] JP 2005-004051 A Summary of the Invention [Problem to be solved by the invention]
[0013] Therefore, an object of the present invention is to provide surface-treated sol-gel silica particles which are subject to minimal change in charge when the environment changes and which, when used as an external toner additive, can impart good printing characteristics to the toner, a method for producing the surface-treated sol-gel silica particles, and an external toner additive comprising the surface-treated sol-gel silica particles. [Means for solving the problem]
[0014] As a result of intensive research conducted by the present inventors in order to achieve the above-mentioned object, it was discovered that surface-treated sol-gel silica particles having specific siloxane units on the surface and having specific particle size, average circularity, refractive index, true density, water vapor adsorption specific surface area / nitrogen adsorption specific surface area ratio and moisture absorptivity, when used as a toner external additive, exhibit little change in charge when the environment changes and impart good printing characteristics to the toner, thereby completing the present invention.
[0015] That is, the present invention provides the following surface-treated sol-gel silica particles, a method for producing the surface-treated sol-gel silica particles, and an external additive for a toner for developing an electrostatic image. [1] On the surface, R 2 SiO 3 / 2 Units (wherein R 2 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and R 4 3SiO 1 / 2 Units (wherein R 4 are the same or different, substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms, (1) The median diameter in dynamic light scattering is 50 nm to 300 nm; (2) The average circularity is 0.80 to 1.0; (3) The refractive index is 1.380 to 1.420, (4) True density is 1.7000g / cm 3 More than 1.9000g / cm 3 is less than (5) Volume resistivity is 10 11 Ω cm or more, (6) the ratio of water vapor adsorption specific surface area / nitrogen adsorption specific surface area is 2.00 to 10.0; (7) The moisture absorption rate when exposed to 30°C / 90% RH for 2 hours is 6.0 to 11% by mass of the dry mass when dried at 150°C for 1 day. Surface treated sol-gel silica particles. [2] R 2 and R 4 The surface-treated sol-gel silica particles according to [1], wherein [3] A method for producing surface-treated sol-gel silica particles according to [1], comprising the following steps (A1) to (A6): Step (A1): A step of obtaining a mixed solvent dispersion of hydrophilic sol-gel silica particles by hydrolyzing and condensing a tetrafunctional silane compound represented by the following formula (I), a partial hydrolysis condensate thereof, or a mixture thereof in a mixed liquid containing a hydrophilic organic solvent and water in the presence of a basic substance. Si(OR 1 )4(I) (In the formula, R 1 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms. Step (A2): A step of replacing the hydrophilic organic solvent in the dispersion medium of the mixed solvent dispersion of hydrophilic sol-gel silica particles obtained in step (A1) with water to obtain an aqueous dispersion of hydrophilic sol-gel silica particles. Step (A3): Refluxing the aqueous dispersion of hydrophilic sol-gel silica particles obtained in step (A2) at the reflux temperature of water for 5 hours or more. Step (A4): A trifunctional silane compound represented by the following formula (II), a partial hydrolysis condensate thereof, or a mixture thereof is added to the aqueous dispersion of the hydrophilic sol-gel silica particles after the step (A3) in an amount of 0.01 to 0.5 mol per mol of Si atoms of the hydrophilic sol-gel silica particles, and R is formed on the surfaces of the hydrophilic sol-gel silica particles. 2 SiO 3 / 2 A step of introducing units to obtain an aqueous dispersion of pre-surface-treated sol-gel silica particles. R 2 Si(OR 3 )3(II) (In the formula, R 2represents a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom, R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms. Step (A5): A step of replacing the dispersion medium of the aqueous dispersion of the pre-surface-treated sol-gel silica particles obtained in step (A4) with a ketone-based solvent to obtain a ketone-based solvent dispersion of the pre-surface-treated sol-gel silica particles. Step (A6): A silazane compound represented by the following formula (III), a monofunctional silane compound represented by the following formula (IV), or a mixture thereof is added in an amount of 0.1 to 0.5 mol per mol of Si atoms of the preliminarily surface-treated sol-gel silica particles to a ketone-based solvent dispersion of the preliminarily surface-treated sol-gel silica particles obtained in step (A5), to form R 4 3SiO 1 / 2 A step of introducing units to obtain surface-treated sol-gel silica particles. R 4 3SiNHSiR 4 3(III) R 4 3SiX (IV) (In the formula, R 4 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms which may be substituted with a halogen atom, and X represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a chlorine atom. [4] R 2 and R 4 The method for producing surface-treated sol-gel silica particles according to [3], wherein [5] [1] or [2], which is an external additive for a toner for developing an electrostatic image, comprising the surface-treated sol-gel silica particles according to the above item [1] or [2]. Effect of the Invention
[0016] The surface-treated sol-gel silica particles of the present invention, when used as an external toner additive, are extremely useful as an external toner additive because they undergo little charge change when the environment changes and provide the toner with good printing characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. [Surface-treated sol-gel silica particles] The surface-treated sol-gel silica particles of the present invention have a surface 2 SiO 3 / 2 Units (wherein R 2 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 6 carbon atoms; and R 4 3SiO 1 / 2 Units (wherein R 4 are the same or different, substituted or unsubstituted monovalent hydrocarbon groups having 1 to 6 carbon atoms.) and the surface-treated sol-gel silica particles satisfy all of the following (1) to (7). (1) The median diameter in dynamic light scattering is 50 nm to 300 nm; (2) The average circularity is 0.8 to 1.0; (3) The refractive index is 1.38 to 1.42; (4) True density is 1.7 g / cm 3 More than 1.9g / cm 3 is less than (5) Volume resistivity is 10 11 Ω cm or more, (6) the ratio of water vapor adsorption specific surface area / nitrogen adsorption specific surface area is 2 to 10; (7) The moisture absorption rate when exposed to 30°C / 90% RH for 2 hours is 6 to 11% by mass relative to the dry mass when dried at 150°C for 1 day.
[0018] R 2 R is a monovalent hydrocarbon group having 1 to 20 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 3 carbon atoms. 2Examples of the monovalent hydrocarbon group represented by the formula (1) include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, hexyl, octyl, and decyl, cycloalkyl groups such as cyclohexyl, alkenyl groups such as vinyl, allyl, n-butenyl, n-hexenyl, and n-octenyl, and aryl groups such as phenyl, with methyl being particularly preferred. In addition, some or all of the hydrogen atoms in these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, preferably with fluorine.
[0019] R 4 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 2 carbon atoms. 3 Examples of the monovalent hydrocarbon group represented by the formula (I) include a methyl group, an ethyl group, a propyl group, a butyl group, a vinyl group, a phenyl group, etc., preferably a methyl group, an ethyl group, a propyl group, and a butyl group, and particularly preferably a methyl group and an ethyl group. In addition, some or all of the hydrogen atoms of these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine atoms, chlorine atoms, and bromine atoms, preferably fluorine atoms.
[0020] The surface-treated sol-gel silica particles of the present invention, which have all of the above physical properties (1) to (7), when used as a toner external additive, exhibit little charge change when the environment changes and impart good printing properties to the toner.
[0021] (1) Median diameter in dynamic light scattering method The median diameter of the surface-treated sol-gel silica particles of the present invention measured by dynamic light scattering is 50 nm to 300 nm, preferably 50 nm to 200 nm. If the median diameter is less than 50 nm, it is not preferable because it cannot exhibit sufficient spacer effect when used as a toner external additive. Also, if the median diameter exceeds 300 nm, it is not preferable because it is easy to cause a decrease in the amount of charge due to a decrease in surface area and a decrease in adhesion to toner particles.
[0022] The median diameter is a value obtained from the volumetric particle size distribution of the surface-treated sol-gel silica particles measured by dynamic light scattering. The dynamic light scattering method is a method of determining the particle size distribution obtained from the scattering intensity by irradiating a dispersion of silica particles with a laser beam using a dynamic light scattering particle size distribution measuring device (e.g., NanotracWave II-Ex150 manufactured by Microtrackbell Co., Ltd.) and utilizing the fact that the scattering intensity of the scattered light obtained varies depending on the particle size of the silica-based fine particles.
[0023] (2) Average circularity The circularity of the surface-treated sol-gel silica particles of the present invention is defined as (perimeter of a circle having an area equal to the particle area / particle perimeter) when the particle is projected two-dimensionally, and the average circularity is the average value of the circularities of 10 arbitrary silica particles observed under a scanning electron microscope. The average circularity of the surface-treated sol-gel silica particles of the present invention is 0.80 to 1.0, and preferably 0.92 to 1.0. If the average circularity is less than 0.80, the proportion of irregularly shaped particles increases, which is undesirable because it is likely to cause toner contamination.
[0024] (3) Refractive index The refractive index indicates the voids inside the surface-treated sol-gel silica particles, and the refractive index is 1.380 to 1.420. If the refractive index is less than 1.380, it is not preferable because it means that there are many voids and the crosslinked structure of the sol-gel silica particles is fragile. Also, if the refractive index exceeds 1.420, it is not preferable because there are few voids and the specific gravity is large, which may reduce the amount of charge or reduce the adhesive force to the toner particles.
[0025] In the present invention, the refractive index of the surface-treated sol-gel silica particles is determined by adding and dispersing the surface-treated sol-gel silica particles in a mixed solvent of toluene (refractive index 1.4962) and methyl isobutyl ketone (refractive index 1.3958), adjusting the refractive index by adjusting the blending ratio of the above solvents, and determining the refractive index of the mixed solvent at the point where the visible light transmittance of the dispersion is highest at 25°C (the point where the refractive index of the mixed solvent and the surface-treated silica fine particles match).
[0026] (4)True density The true density is 1.7000g / cm 3 More than 1.9000g / cm 3 and preferably less than 1.7500 g / cm 3 ~1.8500g / cm 3 The true density is 1.7000g / cm 3 If the true density is less than 1.9000 / cm, the strength of the surface-treated sol-gel silica particles may decrease, which is not preferable. 3 If the weight is more than this, the mass per silica particle becomes large, and therefore when used as an external toner additive, the impact on the toner particles becomes large, which is not preferable.
[0027] (5) Volume resistivity Volume resistivity is an index of insulating and conductive properties of particles. Volume resistivity is 10 11 Ω·cm or more. 10 11 If the resistivity is less than Ω·cm, the conductivity may be exerted, which may adversely affect the toner charging characteristics, and this is not preferable. The upper limit is set to 5.0×10 14 A value of about Ω·cm or less is preferable.
[0028] (6) Ratio of water vapor adsorption specific surface area to nitrogen adsorption specific surface area The ratio of water vapor adsorption specific surface area to nitrogen adsorption specific surface area is a measure of hygroscopicity, and the adsorption specific surface area of each gas can be determined by the BET method. Since water molecules (approximately 2 Å) are smaller than nitrogen molecules (approximately 3 Å), a small ratio of water vapor adsorption specific surface area to nitrogen adsorption specific surface area indicates that water molecules have difficulty passing through, but there are voids large enough for nitrogen to pass through.
[0029] The ratio of the water vapor adsorption specific surface area to the nitrogen adsorption specific surface area is 2.00 to 10.0, and preferably 5.00 to 10.0. If this specific surface area ratio is less than 2.00, the moisture absorption property is poor and the charging environment of the toner cannot be well adjusted, which is not preferable. If it is more than 10.0, the moisture absorption property is too high and the charge amount of the toner is significantly affected by humidity, which is not preferable.
[0030] (7) Moisture absorption rate In the present invention, the moisture absorption rate is a value obtained by measuring the mass (a) of silica particles exposed to conditions of 30°C and 90 RH% for 2 hours and the dry mass (b) of silica particles dried at conditions of 150°C for 1 day, and calculating the percentage of the moisture absorption amount relative to the dry mass [(a)-(b)] / (b)×100 (mass%). The moisture absorption rate of the surface-treated sol-gel silica particles of the present invention is 6.0 to 11 mass%, preferably 9.0 to 11 mass%. If the moisture absorption rate is less than 6.0 mass%, it is not preferable because the charge amount change due to the environmental change cannot be suppressed. On the other hand, if the moisture absorption rate exceeds 11 mass%, it is not preferable because the charge amount tends to decrease.
[0031] [Method of manufacturing surface-treated sol-gel silica particles] The surface-treated sol-gel silica particles of the present invention can be obtained by a production method including the following steps (A1) to (A6). Step (A1): Obtaining a mixed solvent dispersion of hydrophilic sol-gel silica particles Step (A2): Substitution of the dispersion medium with water Step (A3): Heating the aqueous dispersion of hydrophilic sol-gel silica particles Step (A4): Surface treatment step using a trifunctional silane compound Step (A5): Substitution of the dispersion medium with a ketone-based solvent Step (A6): Re-surface treatment step with a monofunctional silane compound
[0032] Step (A1): Obtaining a mixed solvent dispersion of hydrophilic sol-gel silica particles This process is a process in which a tetrafunctional silane compound represented by the following formula (I), its partial hydrolysis condensate, or a mixture thereof is hydrolyzed and condensed in a mixed liquid containing a hydrophilic organic solvent and water in the presence of a basic substance to obtain a mixed solvent dispersion of hydrophilic sol-gel silica particles. Si(OR 1 )4(I) (In the formula, R 1 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms.
[0033] In the above formula (I), R 1R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably having 1 to 4 carbon atoms, and particularly preferably having 1 or 2 carbon atoms. 1 Examples of the monovalent hydrocarbon group represented by the formula (I) include a methyl group, an ethyl group, a propyl group, a butyl group, and a phenyl group. Of these, a methyl group, an ethyl group, a propyl group, and a butyl group are preferred, and a methyl group and an ethyl group are particularly preferred. Examples of the tetrafunctional silane compound represented by the above formula (I) include tetraalkoxysilanes such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane, and tetraphenoxysilane, and preferably tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane, and particularly preferably tetramethoxysilane and tetraethoxysilane. Examples of the hydrolysis condensation product of the tetrafunctional silane compound represented by the above formula (I) include methyl silicate, ethyl silicate, and the like.
[0034] Examples of the basic substance include ammonia, dimethylamine, diethylamine, etc., and preferably ammonia and diethylamine, and particularly preferably ammonia. These basic substances can be used after dissolving the required amount in water.
[0035] The hydrophilic organic solvent is not particularly limited as long as it dissolves the compound represented by the above formula (I) and / or its partial hydrolysis condensate and water, and examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, t-butanol, etc.; ethers such as tetrahydrofuran, dioxane, etc.; glycols such as diethylene glycol, dipropylene glycol, etc., and alcohols are preferred. Since the particle size of the silica particles produced increases as the number of carbon atoms in the alcohol increases, the type of alcohol can be selected depending on the particle size of the desired silica particles.
[0036] The amount of water used in this step is preferably 0.5 to 5 moles, more preferably 0.6 to 2 moles, and particularly preferably 0.7 to 1 mole, per mole of the total of hydrocarbyloxy groups of the tetrafunctional silane compound represented by the above formula (I) and / or its partial hydrolysis condensate. When the above-mentioned basic substance is used by dissolving it in water, the water in which the basic substance is dissolved is also included in the "water" in this step. The ratio of the hydrophilic organic solvent to water is preferably 0.2 to 10, and more preferably 0.3 to 5, in terms of the affinity between the silica particles and the mixed solvent and ease of production. In terms of the size of the resulting silica particles, the amount of the basic substance is preferably 0.01 to 2 mol, and more preferably 0.03 to 0.5 mol, per 1 mol of the total of the hydrocarbyloxy groups of the tetrafunctional silane compound represented by the above formula (I) and / or its partial hydrolysis condensation product.
[0037] The hydrolysis and condensation of the tetrafunctional silane compound or the like can be carried out by a well-known method, that is, by adding the tetrafunctional silane compound and a basic substance to a mixture of a hydrophilic organic solvent and water.
[0038] The temperature during hydrolysis and condensation is preferably 20 to 50° C., and the higher the temperature, the smaller the silica particles that can be obtained.
[0039] The concentration of the hydrophilic sol-gel silica particles obtained in this step (A1) in the mixed solvent dispersion is generally 3 to 15% by mass, and preferably 5 to 10% by mass.
[0040] Step (A2): Substitution of the dispersion medium with water This step is a step of replacing the hydrophilic organic solvent in the mixed solvent dispersion of hydrophilic sol-gel silica particles obtained in step (A1) with water. The hydrophilic organic solvent replaced in step (A2) includes the hydrophilic organic solvent used in step (A1) and volatile by-products such as alcohol generated by condensation. As a replacement method, a thermal concentration method in which the surface-treated colloidal silica obtained in the step (A1) is heated and concentrated while adding water in an amount equal to or greater than the amount of the distillate by heating, or ultrafiltration using a filter can be used to easily and economically obtain an aqueous dispersion.
[0041] The amount of water added is preferably 0.5 to 2 times, and more preferably 0.9 to 1.3 times, in terms of mass ratio, the total amount of the hydrophilic organic solvent used and the alcohol produced, from the viewpoint of the stability of the water-dispersed surface-treated colloidal silica.
[0042] Step (A3): Heating the aqueous dispersion of hydrophilic sol-gel silica particles This step is a step of reacting the aqueous dispersion of hydrophilic sol-gel silica particles obtained in step (A2) at the reflux temperature of water for 5 hours or more, preferably 7 to 12 hours. It is considered that this step promotes hydrolysis (silanolization) of alkoxy groups remaining inside the sol-gel silica particles, and enhances the affinity with water molecules, thereby improving the hygroscopicity of the sol-gel silica particles. The reflux temperature of water can be, for example, 99 to 100°C when step (A3) is performed under 1 atmosphere, but is not limited to the above temperature range when the pressure is different. By this step (A3), it is possible to obtain surface-treated sol-gel silica particles that satisfy the desired ratio of the water vapor adsorption specific surface area / nitrogen adsorption specific surface area (6) and the desired moisture absorption rate (7).
[0043] Step (A4): Surface treatment step using a trifunctional silane compound In this step, a trifunctional silane compound represented by the following formula (II), a partial hydrolysis condensate thereof, or a mixture thereof is added to the aqueous dispersion of the hydrophilic sol-gel silica particles after the step (A3), and R is formed on the surface of the sol-gel silica particles. 2 SiO 3 / 2 This is the step of introducing the units to obtain an aqueous dispersion of preliminarily surface-treated sol-gel silica particles. R 2 Si(OR 3 )3(II) (In the formula, R 2represents a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom, R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms.
[0044] In the above formula (II), R 2 R is a monovalent hydrocarbon group having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, and particularly preferably 1 to 3 carbon atoms. 2 Examples of the monovalent hydrocarbon group represented by the formula (I) include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, hexyl, octyl, and decyl, and particularly preferred are methyl, ethyl, and propyl. Some or all of the hydrogen atoms in these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, preferably fluorine atoms.
[0045] In the above formula (II), R 3 R is a monovalent hydrocarbon group having 1 to 6 carbon atoms, preferably having 1 to 4 carbon atoms, and particularly preferably having 1 or 2 carbon atoms. 3 Examples of the monovalent hydrocarbon group represented by the formula (I) include a methyl group, an ethyl group, a propyl group, a butyl group, and a phenyl group. Of these, a methyl group, an ethyl group, a propyl group, and a butyl group are preferred, and a methyl group and an ethyl group are particularly preferred.
[0046] Specific examples of the trifunctional silane compound represented by the above formula (II) include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, i-propyltrimethoxysilane, i-propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, (heptadecafluoro-1,1,2,2-tetrahydrodecyl)trimethoxysilane, and the like.
[0047] The amount of the trifunctional silane compound represented by the above formula (II) used is 0.01 to 0.5 mol, preferably 0.01 to 0.1 mol, per mol of Si atoms in the hydrophilic sol-gel silica particles.
[0048] The reaction conditions in this step (A4) are not limited, but a reaction temperature of 20 to 60° C. and a reaction time of 1 to 24 hours are preferred.
[0049] Step (A5): Substitution of the dispersion medium with a ketone-based solvent This step is a step of replacing the dispersion medium composed of water, a hydrophilic organic solvent, and volatile by-products such as alcohol produced by condensation in the aqueous dispersion of the preliminarily surface-treated sol-gel silica particles obtained in step (A4) with a ketone-based solvent.
[0050] Specific examples of the ketone solvent include methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, etc., and preferably methyl isobutyl ketone.
[0051] The amount of the ketone solvent added is preferably 0.5 to 5 times, more preferably 1 to 2 times, by mass ratio relative to the pre-surface-treated sol-gel silica particles obtained in step (A4), from the viewpoints of suppressing aggregation of the silica particles and the concentration of the reaction system in the subsequent surface treatment step using a monofunctional silane compound.
[0052] Methods for replacing the hydrophilic organic solvent, water, and volatile by-products such as alcohol generated by condensation in the hydrophobic spherical silica particle dispersion with a ketone solvent include concentration (atmospheric pressure or reduced pressure), ultrafiltration using a filter, etc. A preferred method is to add a ketone solvent having a boiling point higher than that of the water and hydrophilic organic solvent contained in the aqueous dispersion of the preliminary surface-treated sol-gel silica particles obtained in step (A4) to the aqueous dispersion of the preliminary surface-treated sol-gel silica particles obtained in step (A4), and then concentrate the mixture.
[0053] Step (A6): Re-surface treatment step with a monofunctional silane compound In this step, a silazane compound represented by the following formula (III), a monofunctional silane compound represented by the following formula (IV), or a mixture thereof is added in an amount of 0.1 to 0.5 mol per mol of Si atoms of the preliminarily surface-treated sol-gel silica particles to a ketone-based solvent dispersion of the preliminarily surface-treated sol-gel silica particles obtained in step (A5), and R is formed on the surfaces of the preliminarily surface-treated sol-gel silica particles. 4 3SiO 1 / 2 This is the step of introducing the unit to obtain surface-treated sol-gel silica particles. R 4 3SiNHSiR 4 3(III) R 4 3SiX (IV) (In the formula, R 4 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms which may be substituted with a halogen atom, and X represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a chlorine atom.
[0054] In the above formulas (III) and (IV), R 4 R is preferably a monovalent hydrocarbon group having 1 to 4 carbon atoms, and particularly preferably 1 to 2 carbon atoms. 4 Examples of the monovalent hydrocarbon group represented by the formula (I) include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl, and are preferably methyl, ethyl, and propyl, and more preferably methyl and ethyl. Some or all of the hydrogen atoms in these monovalent hydrocarbon groups may be substituted with halogen atoms such as fluorine, chlorine, and bromine, and preferably fluorine atoms.
[0055] The alkoxy group represented by X is preferably one having 1 to 4 carbon atoms, and particularly preferably a methoxy group or an ethoxy group.
[0056] Examples of the silazane compound represented by the above formula (III) include hexamethyldisilazane, hexaethyldisilazane, etc., and preferably hexamethyldisilazane. Examples of the monofunctional silane compound represented by the above formula (IV) include monosilanol compounds such as trimethylsilanol and triethylsilanol; monochlorosilanes such as trimethylchlorosilane and triethylchlorosilane; monoalkoxysilanes such as trimethylmethoxysilane and trimethylethoxysilane, and preferably trimethylsilanol and trimethylmethoxysilane.
[0057] The amount of the compounds represented by the above formulae (III) and (IV) used is preferably 0.1 to 0.5 mol, more preferably 0.2 to 0.4 mol, and particularly preferably 0.25 to 0.35 mol, per mol of Si atoms in the above preliminary surface-treated sol-gel silica particles. Within such a range, good positive charging properties, environmental charging properties, and flowability can be obtained.
[0058] The reaction conditions for the surface treatment in step (A6) are preferably a reaction temperature of 40 to 130° C. and a reaction time of 1 to 10 hours, more preferably a reaction temperature of 60 to 120° C. and a reaction time of 2 to 8 hours.
[0059] After the reaction, the ketone-based solvent, water, alcohol, and other volatile by-products are appropriately removed from the ketone-based solvent dispersion of the surface-treated sol-gel silica particles to obtain the surface-treated sol-gel silica particles.
[0060] [Toner additive for electrostatic image development] The surface-treated sol-gel silica particles of the present invention can be suitably used as a toner external additive, particularly as a toner external additive for developing electrostatic images. The amount of the toner external additive using the surface-treated sol-gel silica particles of the present invention to be blended with the toner is preferably 0.01 to 20 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the toner. If the blending amount is 0.01 parts by mass or more, the amount of adhesion to the toner is sufficient, and sufficient toner fluidity is obtained, so this is preferable, and if it is 20 parts by mass or less, it has a favorable effect on the chargeability of the toner and is also economically preferable. The toner to which the electrostatic image developing toner external additive made of the surface-treated sol-gel silica particles of the present invention is added may be a known toner composed mainly of a binder resin and a colorant. If necessary, a charge control agent may be added. The toner may be used as a one-component developer, but may also be used as a two-component developer by mixing the toner with a carrier. When used as a two-component developer, the electrostatic image developing toner external additive of the present invention may not be added to the toner in advance, but may be added when the toner and carrier are mixed to coat the surface of the toner. As the carrier, iron powder or a known one having a resin coating on its surface is used. EXAMPLES
[0061] The present invention will be specifically described below using examples and comparative examples. Note that the following examples do not limit the present invention in any way. Various evaluations such as particle size distribution measurement and particle shape observation of the silica particles obtained in the examples and comparative examples were performed under the following conditions, and the results are shown in Table 1.
[0062] [(1) Median diameter in dynamic light scattering method] The silica particle dispersion was diluted with methanol so that the silica particles were 0.5% by mass, and the particle size distribution when the dispersion was irradiated with ultrasound for 10 minutes was measured using a particle size distribution measuring device (Microtrack Bell, Nanotrac Wave II-EX150) using a dynamic light scattering method. Based on the obtained volumetric particle size distribution, the median diameter was calculated.
[0063] [(2) Average circularity] The silica particles were observed and their shapes were confirmed using a field emission scanning electron microscope (S-4700, Hitachi High-Technologies Corporation). The circularity of the particles projected two-dimensionally was calculated as (perimeter of a circle equal to the particle area) / (particle perimeter), and the average circularity of 10 silica particles was taken as the average circularity.
[0064] [(3) Refractive index] 1 g of surface-treated silica particles was added and dispersed in 20 g of a mixed solvent of toluene (refractive index 1.4962) and methyl isobutyl ketone (refractive index 1.3958). The refractive index was adjusted by the blending ratio of the above solvents, and the refractive index of the mixed solvent when the visible light transmittance of the dispersion was the highest was taken as the refractive index of the silica particles. The refractive index of the mixed solvent was a value measured at 25°C using a digital refractometer (Atago RX-9000α), and the visible light transmittance of the dispersion was the average value of the light transmittance at wavelengths of 380 to 780 nm measured at 25°C using a spectrophotometer (Hitachi High-Tech Science U-3900H).
[0065] [(4) True density] The true density of the silica particles was measured using an automatic true density measuring device (Auto True Denser MAT-7000, manufactured by Seishin Enterprise Co., Ltd.) that uses a liquid phase displacement method.
[0066] [(5) Volume resistivity] Using a powder resistivity system (MCP-PD51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.), the volume resistivity of the silica particles under a load of 4.0 kN was measured using a four-probe electrode unit.
[0067] [(6) Ratio of water vapor adsorption specific surface area to nitrogen adsorption specific surface area] Using a high-precision gas adsorption measurement device (BELSORP MAX II manufactured by MicrotrackBell), the specific surface areas of the silica particles for both water vapor and nitrogen media were measured by the BET single-point method, and the ratio of water vapor adsorption specific surface area / nitrogen adsorption specific surface area was calculated.
[0068] [(7) Moisture absorption rate] The mass (a) of silica particles exposed to conditions of 30°C and 90 RH% for 2 hours and the dry mass (b) of silica particles dried at 150°C for 1 day were measured, and the moisture absorption rate relative to the dry mass was calculated as [(a)-(b)] / (b) x 100 (mass%).
[0069] [Example 1-1] Step (A1): Obtaining a mixed solvent dispersion of hydrophilic sol-gel silica particles In a 3-liter glass reactor equipped with a stirrer, a dropping funnel, and a thermometer, 623.7 g of methanol, 41.4 g of water, and 49.8 g of 28% aqueous ammonia were mixed. The solution was adjusted to 35°C, and while stirring, 1163.7 g (7.66 moles) of tetramethoxysilane and 418.1 g of 5.4% aqueous ammonia were simultaneously added dropwise, the former over 6 hours and the latter over 4 hours. After the addition was completed, stirring was continued for another 0.5 hours to carry out hydrolysis, and 2,295 g of a mixed solvent dispersion of hydrophilic sol-gel silica particles was obtained.
[0070] Step (A2): Substitution of the dispersion medium into water An ester adapter and a cooling tube were attached to the reaction vessel after the above step (A1), and the vessel was heated to 60 to 70°C until 1,132 g of methanol was distilled off, at which point 1,200 g of water was added, and the vessel was then heated to 70 to 90°C until 273 g of methanol was distilled off, to obtain an aqueous dispersion of hydrophilic sol-gel silica particles.
[0071] Step (A3): Heating the aqueous dispersion of hydrophilic sol-gel silica particles After the above step (A2), the internal temperature of the aqueous dispersion of hydrophilic sol-gel silica particles was kept at 99 to 100° C., and the mixture was stirred for 10 hours under reflux.
[0072] Step (A4): Surface treatment step using a trifunctional silane compound After step (A3) above, 11.6 g of methyltrimethoxysilane (equivalent to 0.1 mole per mole of Si atoms in silica) was added dropwise to the reaction vessel at 25°C over a period of 0.5 hours, and the mixture was stirred at 25°C for 12 hours to obtain an aqueous dispersion of pre-surface-treated sol-gel silica particles.
[0073] Step (A5): Replacement of the dispersion medium with a ketone-based solvent To the reaction vessel after step (A4) above, 1440 g of methyl isobutyl ketone was added at 25° C. The mixture was heated to 80 to 110° C., and the mixture of methanol and water was distilled off over 10 hours to obtain a ketone-based solvent dispersion of preliminary surface-treated sol-gel silica particles.
[0074] Step (A6): Re-surface treatment step using a monofunctional silane compound After the step (A5), 357.6 g of hexamethyldisilazane (0.29 moles per mole of Si atom in silica) was added to the reaction vessel at 25° C., and the reaction was carried out for 8 hours at a reaction temperature of 120° C., thereby carrying out trimethylsilylation of the silica particle surface. The dispersion medium was then distilled off under reduced pressure to obtain 470 g of white surface-treated sol-gel silica particles (i).
[0075] [Example 1-2] Surface-treated sol-gel silica particles (ii) 463 g were obtained in the same manner as in Example 1-1, except that in step (A1) of Example 1-1, the reaction temperature was set to 42°C, and in step (A3), the time for stirring under reflux was set to 12 hours.
[0076] [Examples 1-3] Surface-treated sol-gel silica particles (iii) 471 g were obtained in the same manner as in Example 1-1, except that in step (A1) of Example 1-1, the reaction temperature was 45°C, and in step (A3), the time for stirring under reflux was 11 hours.
[0077] [Examples 1-4] 468 g of surface-treated sol-gel silica particles (iv) were obtained in the same manner as in Example 1-1, except that in step (A1) of Example 1-1, the reaction temperature was set to 25°C, and in step (A3), the time for stirring under reflux was set to 9 hours.
[0078] [Comparative Example 1-1] The same procedure as in Example 1-1 was carried out except that the step (A3) in Example 1-1 was not carried out, to obtain 474 g of surface-treated sol-gel silica particles (v).
[0079] [Comparative Example 1-2] The same procedure as in Example 1-1 was conducted except that in step (A3) of Example 1-1, the time for stirring under reflux was changed to 4 hours, thereby obtaining 472 g of surface-treated sol-gel silica particles (vi).
[0080] [Table 1]
[0081] As shown in Table 1, the surface-treated sol-gel silica particles of Examples 1-1 to 1-4 exhibited high hygroscopicity. On the other hand, in Comparative Examples 1-1 and 1-2, the water vapor adsorption specific surface area / nitrogen adsorption specific surface area ratio was small, resulting in poor hygroscopicity.
[0082] [Examples 2-1 to 2-4, Comparative Examples 2-1 and 2-2] (Production of toner containing additives) 96 parts by mass of polyester resin with a Tg of 60°C and a softening point of 110°C and 4 parts by mass of Carmine 6BC (manufactured by Sumika Color Co., Ltd.) as a coloring agent were melt-kneaded, pulverized, and classified to obtain a toner with a volume median diameter of 7 μm. 10 g of this toner was mixed with 0.2 g of each of the surface-treated sol-gel silica particles obtained in Examples 1-1 to 1-4 and Comparative Examples 1-1 and 1-2 in a sample mill to obtain a toner mixed with an external additive.
[0083] (Preparation of Two-Component Developer) A two-component developer was prepared by mixing 3 parts by mass of the above-mentioned external additive mixed toner with 97 parts by mass of ferrite (EL-35, manufactured by Powder Tech Co., Ltd.) as a carrier. The two-component developer obtained by the above process was measured according to the following methods (8) to (12), and the results are shown in Table 2.
[0084] (8) Toner Charge Amount The above two-component developer was exposed to high temperature and high humidity (30°C, 90% RH) and low temperature and low humidity (10°C, 15% RH) conditions for one day, and then the charge amount when each sample was triboelectrically charged under the same conditions was measured using a blow-off powder charge amount measuring device (TB-200, manufactured by Toshiba Chemical Corporation).
[0085] (9) Toner adhesion to the photoconductor The two-component developer was placed in a developing machine equipped with an organic photoconductor, and a print test of 30,000 sheets was carried out under an environment of 25°C and 50% RH. At this time, the adhesion of the toner to the photoconductor can be sensed as a blank area in the entire solid image. Here, the degree of blank area is 1 cm2 A number of blank spots per unit was rated as "many" if it was 10 or more, "few" if it was 1 to 9, and "none" if it was 0.
[0086] (10) Photoconductor wear In the print test (9) above, the wear of the photoreceptor, which is detected as image distortion, was evaluated according to the following criteria. A: No image distortion B: No significant image distortion C: Images with distortion
[0087] (11) Image defect (white spot) evaluation The two-component developer was exposed to an environment of 30°C and 90% RH for one day, and then 5,000 solid prints (image density 100%) of 20 cm square were printed continuously, after which the two-component developer was again left stationary in an environment of 30°C and 90% RH. This was repeated 60 times, resulting in a total of 300,000 prints. The 10th print on the first day was Print 1, and the final print on the last day was Print 2.
[0088] The print 2 obtained above was observed for the presence or absence of image defects (white spots) and evaluated according to the following criteria. A: No visible image defects (no white spots) B: Visually inspected white spots (grainy white spots) 1 to 4 C: 5 to 9 white spots visible D: 10 or more white dots visible
[0089] (12) Evaluation of concentration change (ΔE) The density change of print 2 relative to print 1 was measured using a reflection densitometer X-rite 938 (manufactured by X-rite) in the CIE 1976 (L*a*b*) color space in accordance with JIS Z 8781-5, and evaluated according to the following criteria. A: ΔE difference is less than 1 B: ΔE difference is 1 or more and less than 2.5 C: ΔE difference is 2.5 or more and less than 3.0 D: ΔE difference is 3.0 or more
[0090] [Table 2]
[0091] As shown in Table 2, the two-component developer using the surface-treated sol-gel silica particles obtained in Examples 1-1 to 1-4 as a toner external additive showed a small change in the toner charge amount depending on the environment and produced no print image defects. The surface-treated sol-gel silica particles of the present invention have a moderate hygroscopicity, and therefore, in a high humidity environment, it is believed that the surface-treated sol-gel silica particles absorb moisture in the environment near the toner particle surface to suppress the decrease in the charge amount, and in a low humidity environment, the moisture held inside the silica particles is released to reduce the environmental change near the toner particle surface. On the other hand, the two-component developers using the surface-treated sol-gel silica particles obtained in Comparative Examples 1-1 and 1-2 as a toner external additive exhibited large fluctuations in the toner charge amount due to environmental factors and poor printing characteristics.
Claims
1. On the surface, R 2 SiO 3 / 2 Units (wherein R 2 is a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom; and R 4 3 SiO 1 / 2 Units (wherein R 4 are independently a monovalent hydrocarbon group having 1 to 6 carbon atoms which may be substituted with a halogen atom, (1) The median diameter measured by dynamic light scattering is 50 nm to 300 nm; (2) The average circularity is 0.80 to 1.0; (3) the refractive index is 1.380 to 1.420; (4) True density is 1.7000 g / cm 3 More than 1.9000g / cm 3 is less than (5) Volume resistivity is 10 11 Ω cm or more, (6) the ratio of water vapor adsorption specific surface area / nitrogen adsorption specific surface area is 2.00 to 10.0; (7) The moisture absorption rate when exposed to 30°C / 90% RH for 2 hours is 6.0 to 11% by mass based on the dry mass when dried at 150°C for 1 day. Surface treated sol-gel silica particles.
2. The R 2 and R 4 2. The surface-treated sol-gel silica particles according to claim 1, wherein is a methyl group.
3. The method for producing surface-treated sol-gel silica particles according to claim 1, comprising the following steps (A1) to (A6): Step (A1): A step of obtaining a mixed solvent dispersion of hydrophilic sol-gel silica particles by hydrolyzing and condensing a tetrafunctional silane compound represented by the following formula (I), a partial hydrolysis condensate thereof, or a mixture thereof in a mixed liquid containing a hydrophilic organic solvent and water in the presence of a basic substance. Si(OR 1 ) 4 (I) (In the formula, R 1 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms. Step (A2): A step of replacing the hydrophilic organic solvent in the dispersion medium of the mixed solvent dispersion of hydrophilic sol-gel silica particles obtained in step (A1) with water to obtain an aqueous dispersion of hydrophilic sol-gel silica particles. Step (A3): A step of refluxing the aqueous dispersion of hydrophilic sol-gel silica particles obtained in step (A2) at the reflux temperature of water for 5 hours or more. Step (A4): A trifunctional silane compound represented by the following formula (II), a partial hydrolysis condensate thereof, or a mixture thereof is added to the aqueous dispersion of the hydrophilic sol-gel silica particles after step (A3) in an amount of 0.01 to 0.5 mol per mol of Si atoms of the hydrophilic sol-gel silica particles, to form R on the surfaces of the hydrophilic sol-gel silica particles. 2 SiO 3 / 2 A step of introducing units to obtain an aqueous dispersion of pre-surface treated sol-gel silica particles. R 2 Si (OR 3 ) 3 (II) (In the formula, R 2 represents a monovalent hydrocarbon group having 1 to 20 carbon atoms which may be substituted with a halogen atom; R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms. Step (A5): A step of replacing the dispersion medium of the aqueous dispersion of the preliminarily surface-treated sol-gel silica particles obtained in step (A4) with a ketone-based solvent to obtain a ketone-based solvent dispersion of the preliminarily surface-treated sol-gel silica particles. Step (A6): A silazane compound represented by the following formula (III), a monofunctional silane compound represented by the following formula (IV), or a mixture thereof is added in an amount of 0.1 to 0.5 mol per mol of Si atoms of the preliminarily surface-treated sol-gel silica particles to a ketone-based solvent dispersion of the preliminarily surface-treated sol-gel silica particles obtained in step (A5), to form R 4 3 SiO 1 / 2 A step of introducing units to obtain surface-treated sol-gel silica particles. R 4 3 SiNHSiR 4 3 (III) R 4 3 SiX (IV) (In the formula, R 4 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms which may be substituted with a halogen atom, and X represents a hydroxyl group, an alkoxy group having 1 to 6 carbon atoms, or a chlorine atom.
4. R 2 and R 4 The method for producing surface-treated sol-gel silica particles according to claim 3, wherein is a methyl group.
5. 3. An external additive for a toner for developing electrostatic images, comprising the surface-treated sol-gel silica particles according to claim 1 or 2.
Citation Information
Patent Citations
Highly hydrophobic spherical sol-gel silica fine particle, method for producing the same, toner external additive for electrostatic charge image development composed of the fine particle, and developer using the toner external additive
JP2007099582A
Surface-hydrophobized spherical silica fine particle, method for producing the same, and toner external additive, obtained by using the particle, for developing electrostatic charge image
JP2014114175A
Surface organic resin-coated hydrophobic spherical silica fine particle, production method of the same, and toner external additive for electrostatic charge image development using the same
JP2015059054A
Hydrophobic silica for electrophotographic toner composition
JP2017124965A
Positive charge type hydrophobic spherical silica particle, method for producing the same, and positive charge toner composition using the same
JP2020033224A